Anti-angiogenic Agents in Combination With Immune Checkpoint Inhibitors: A Promising Strategy for Cancer Treatment - Song, Yuxiao; Fu, Yang; Xie, Qi; Zhu, Bo; Wang, Jun; Zhang, Bicheng (Frontiers in Immunology, 2020)
Advances in cancer immunity have promoted a major breakthrough in the field of cancer therapy. This is mainly associated with the successful development of immune checkpoint inhibitors (ICIs) in multiple human tumor types. Blockade with different ICIs, including programmed cell death 1 (PD-1), programmed cell death ligand 1 (PD-L1) and cytotoxic T-lymphocyte-associated protein 4 (CTLA-4) inhibitors, may activate the host’s immune system against malignant cells. However, only a subgroup of cancer patients would benefit from immune checkpoint blockade. Some patients experience primary resistance to initial immunotherapy, and a majority of patients eventually develop acquired resistance to ICIs, whereas the mechanisms attributable to drug resistance to immune checkpoint blockade remain unclear. Recent studies supported that combination of ICIs and anti-angiogenic agents could be a promising therapeutic strategy to solve the low efficacy of ICIs. Besides the direct anti-cancer effect by inhibiting tumor growth and metastasis, anti-angiogenic drugs reprogram the tumor milieu from an immunosuppressive to an immune permissive microenvironment. Activated immunity by immune checkpoint blockade also facilitates anti-angiogenesis by downregulating the expression of vascular endothelial growth factor and alleviating hypoxia condition. Many clinical trials showed an improved anti-cancer efficacy and prolonged survival when anti-angiogenic agents were added to ICIs. This review summarized the understanding and clinical development of combination therapy with immune checkpoint blockade and anti-angiogenic strategy.